Desempenho e características de carcaça de cordeiros alimentados com fontes de carboidratos associadas ao óleo de girassol - Morgado, Eliane da Silva [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP]; Galzerano, Leandro [UNESP]; Silva Sobrinho, Américo Garcia da [UNESP] (My University, 2013)
This work was carried out with the objective to evaluate the effect of different carbohydrate sources associated with sunflower oil on performance, carcass characteristics and cuts yields of feedlot sheep. Twenty four lambs were assigned to a completely randomized design with a 2 × 2 factorial arrangement with two sources of neutral detergent soluble carbohydrate, starch or neutral detergent soluble fiber, with and without the inclusion of 4.2% sunflower oil. The treatments consisted of diets containing high content of soluble fiber (17.14% DM) without adding oil, high in soluble fiber (16.35% DM) with inclusion of 4.2% sunflower oil, high starch (30.14% DM) without adding oil and high starch (28.21% DM) with addition of 4.2% of sunflower oil. The animals were feedlot with average initial of 17.7 kg and when reached 35 kg body weight were slaughtered. The different sources of carbohydrate and oil inclusion in the diet not influence the days on feedlot in the dry matter intake and average daily weight gain, but higher feed conversion was observed for the diet with a high percentage of neutral detergent soluble fiber compared to diet high in starch. The carcass weights and yields as well as the commercial cuts were not affected by diets. The performance and quantitative characteristics and carcass cuts of lamb are not affected by different carbohydrate sources and their association with 4.2% sunflower oil.

Objetivou-se avaliar o efeito de diferentes fontes de carboidratos associadas ao óleo de girassol sobre o desempenho, as características quantitativas e rendimento dos cortes da carcaça de ovinos confinados. Vinte quatro cordeiros foram distribuídos em delineamento inteiramente ao acaso, em esquema fatorial 2 × 2, com duas fontes de carboidratos (amido ou fibra solúvel em detergente neutro), com ou sem a inclusão de 4,2% de óleo de girassol. Os tratamentos foram constituídos por dietas com: alta fibra solúvel (17,14% na MS) sem inclusão de óleo, alta fibra solúvel (16,35% na MS) com inclusão de 4,2% de óleo de girassol, alto amido (30,14% na MS) sem inclusão de óleo e alto amido (28,21% na MS) com inclusão de 4,2% de óleo de girassol. Os animais iniciaram o experimento com peso corporal médio de 17,7 kg ± 2,6 kg e ao atingirem 35 kg de peso corporal foram abatidos. As diferentes fontes de carboidratos e a inclusão de óleo às dietas não influenciaram no tempo de confinamento, no consumo de matéria seca e no ganho de peso médio diário, porém pior conversão alimentar foi verificada para a dieta com elevado percentual de fibra solúvel em detergente neutro em comparação à dieta com elevado teor de amido. Os rendimentos da carcaça, assim como os cortes comerciais não foram influenciados pelas dietas. O desempenho, as características quantitativas e os cortes da carcaça dos cordeiros não são afetados pelas diferentes fontes de carboidratos e por suas associações com 4,2% de óleo de girassol.
Performance and carcass characteristics of lambs fed with carbohydrate sources associated to sunflower oil
Keywords: Carcass dressing; Citrus pulp; Commercial cuts; Corn; Feedlot; Ovis Aires